2008
DOI: 10.1093/bja/aen270
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen concentrate substitution therapy in patients with massive haemorrhage and low plasma fibrinogen concentrations

Abstract: Off-label substitution therapy with a fibrinogen concentrate generally improved global laboratory coagulation results and as supplementary intervention, appeared to diminish the requirements for RBC, FFP, and platelet substitution in this patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 15 publications
7
182
3
5
Order By: Relevance
“…Maintaining fibrinogen levels is an important therapeutic target in bleeding patients, particularly in perioperative settings. [1][2][3] Early studies demonstrated that fibrinogen repletion corrected clot strength, based on viscoelastic blood testing using thromboelastography/thromboelastometry. 4 Normal fibrinogen levels are elevated during pregnancy, 5 and cases studies indicate that fibrinogen repletion may be effective in the treatment of postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining fibrinogen levels is an important therapeutic target in bleeding patients, particularly in perioperative settings. [1][2][3] Early studies demonstrated that fibrinogen repletion corrected clot strength, based on viscoelastic blood testing using thromboelastography/thromboelastometry. 4 Normal fibrinogen levels are elevated during pregnancy, 5 and cases studies indicate that fibrinogen repletion may be effective in the treatment of postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with fresh frozen plasma, the efficacy of fibrinogen concentrate in the recovery of plasma fibrinogen levels and subsequent hemostasis was reported in hereditary and acquired hypofibrinogenemia,13 including those derived from trauma 14, 15. Encouraged by the volume of pharmacovigilance data showing the safety profile for fibrinogen concentrate,16 off‐label use of the concentrate in Japan to treat massive hemorrhage during aortic surgery17 and obstetrical emergencies has been reported 18.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is a coagulation protein produced by the liver that helps the body in the formation of blood clots. The normal range of fibrinogen is 2–4 g/L, but the concentration increases up to threefold in the presence of an inflammatory process, infection, or tissue damage (Fenger‐Eriksen, Lindberg‐Larsen, Christensen, Ingerslev, & Sørensen, 2008; Gruys et al, 2005; Schmaier, 2012). High concentrations of fibrinogen are also strongly associated with chronic obstructive pulmonary diseases and moderately with coronary heart diseases (Danesh et al, 2005; Duvoix et al, 2013; Mannino et al, 2015).…”
Section: Methodsmentioning
confidence: 99%